A Study of the Natural Immune Reaction to Mycobacterial Isolates of Human: Examining the Role of Interferons in Tuberculosis and Therapy Response (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Mycobacterium tuberculosis (M. tb) causes TB and kills millions worldwide. Immune-dependenttissue-damaging inflammation promotes aerosol transmission, making this disease ubiquitous. SinceType I IFNs play a debatable role in TB and their induction precedes clinical tuberculosis in patients, thisstudy sought to identify a pattern (absolute levels and relative ratios) in interferon and regulatory moleculeexpression levels that correspond with TB patients and pulmonary versus extra pulmonary TB. Using an invitro M. tb THP-1 infection model and antibody-based neutralization of specific interferons, we found thatmodulating interferon production promotes intracellular bacterial burden or clearance.Real-time PCR was performed to compare IFN alpha, beta, and gamma fold mRNA expression in 123untreated TB patients (PTB - 56 EPTB - 67) and 86 healthy family contacts clinically clear of TB. EPTBand PTB patients' three IFN expression levels were compared. ELISA for Interleukin-1β, -1α, andProstaglandin E2 was done on sera from 62 TB patients and 18 healthy contacts from the sameresidence.TB patients expressed more IFN-α than counterparts. IFN-α had the highest median fold mRNAexpression (0.80) in untreated TB patients. PTB patients had a median fold mRNA expression level ofIFN- (0.87) that was higher than EPTB patients'. EPTB patients expressed 0.81 times more IFN-α thanPTB patients. The three IFNs were measured in matched samples from each patient at enrolment andafter treatment. IFN-β and IFN- reduced considerably after therapy. IFN-α high or IFN-β low patients andcontacts were then identified. All samples tested by ELISA had IFN- levels below detection. Every samplehas PGE2. IL-1 detection vary. PGE2 and IFN- levels were found inversely correlated. These data suggestmeasuring type I IFNs may help monitor therapy response. The pattern of IFNs in patients (host factors)and the identification of acid-fast bacilli (AFB) by conventional smear microscopy (mycobacterialfactors) are expected to occur earlier and precede mycobacterial load reduction.